Wellness Coaching dengan Smile Model terhadap Kepatuhan Pembatasan Intake Cairan dan Fungsi Ginjal pada Pasien Gagal Ginjal Kronik yang Menjalani Hemodialisa - Teten Rustendi; Iin Inayah; Susilawati Susilawati; Blacius Dedi; Murtiningsih Murtiningsih (Jurnal Keperawatan Silampari, 2022)
This study aims to determine the effect of wellness coaching with the smiling model on adherence to fluid intake restrictions and kidney function in CRF patients undergoing hemodialysis at the Hemodialysis Installation at Puri Asih Karawang General Hospital. This research is a quasi-experimental study using a pre-test and post-test design with a control group design. The results showed that before the intervention, the abnormal kidney function (urea) group had a higher pre-test, namely 20 respondents (87%), and in the urea control group, there were 18 respondents (78.3%). The creatinine values ​​for the intervention group and the control group were almost comparable to typical values, namely, 17 respondents (73.9) in the intervention group and 18 respondents (82.6%) in the control group. As for after the intervention, it can be seen that after the intervention in the intervention group, most of the kidney function of urea was higher, namely 18 respondents (78.3%), and in the urea control group, there were 13 respondents (56.5%). The creatinine value for the intervention and control groups was dominated by average values, namely 16 respondents (69.6%) and 19 respondents (82.6%). In conclusion, there is an effect of wellness coaching on compliance with fluid intake restrictions and no impact on kidney function. Still, there is no difference in adherence and kidney function between the intervention and control groups. Keywords: Coaching Wellness, Kidney Function, Compliance, Smile Model